The effect of non-thermal plasma on the adhesion of resin cement to zirconia ceramic / Mohd Azmi Abdul Razak - Mohd Azmi , Abdul Razak (2017)
Aim: The aim of this in vitro study was to investigate the effect of non-thermal plasma on zirconia towards resin-zirconia bond strength and its durability using three different systems of adhesive resin cement. Methodology: Sixty zirconia (Y-TZP) discs were divided into six groups with twenty specimens each (n=20/group) and were subjected to two different surface treatments: 1) Control group: Sandblast and primer (SB); 2) Test group: Sandblast, non-thermal plasma for 60 seconds and then primer (SB+NTP). Resin cylinders were then bonded on the discs using three different adhesive resin cements; Panavia™V5, Multilink®Automix, and RelyX™Ultimate utilizing its recommended primer. Half of the specimens from each group were tested after 24 hours polymerisation, and the other half were tested after aging process with water storage (48 hours, 37ºC) and thermocycling (5000 cycles) using microshear bond test. Data were analysed with Linear Mixed Model and Šídák’s test for multiple comparisons (α = 0.05) and failed specimens were examined for failure mode under a Tandom Scanning Microscope. Results: Multiple comparison with Šídák’s test revealed no statistically significant difference between test (SB+NTP) groups and control groups (SB) (p<0.05). However, a statistically significant difference was found between Multilink SB and Rely X SB groups, as well as between short-term (ST) and long-term (LT) groups (p<0.05). Predominant failure modes were found to be cohesive. Conclusion: Non-thermal plasma application as added surface modification to current technique had no significant effect on the resin-zirconia bond strength or its durability. Aging process with water storage and thermocycling played an important role in resin-zirconia bonds degradation.